Evaluation of carotid artery elasticity and its influencing factors in non-obese PCOS patients using a technique for quantitative vascular elasticity measurement - Hu, Yanli; Chen, Bo; Pan, Yingzheng; Xing, Kewei; Xiao, Zhibo; Sheng, Bo; Li, Jia; Dong, Hongmei; Lv, Furong (Frontiers in Endocrinology, 2024)
Objectives To evaluate the intima-media thickness (IMT) and elasticity of the carotid artery in non-obese polycystic ovary syndrome (PCOS) patients using a quantitative technique for vascular elasticity measurement and to explore the influencing factors. Methods Sixty non-obese patients without metabolic and cardiovascular diseases who were diagnosed with PCOS in the Women and Children’s Hospital of Chongqing Medical University from January to December 2022 were prospectively selected (case group), and 60 healthy volunteers matched for body mass index were included as the control group. Body weight, height, heart rate, blood pressure, and waist-to-hip ratio were recorded. Fasting blood samples were drawn from the elbow vein to measure hormone levels including total testosterone (TT), sex hormone-binding globulin (SHBG), fasting plasma glucose (FPG), fasting insulin (FINS), lipids, and homocysteine (Hcy). The insulin resistance index (HOMA-IR) and free androgen index (FAI) were calculated. Ultrasound elastography was used to measure the IMT and elastic function parameters of the right carotid artery, including vessel diameter, wall displacement, stiffness coefficient, and pulse wave velocity. Differences in various parameters between the two groups were analyzed, and correlations between the carotid stiffness coefficient and other serological indicators were assessed using Spearman correlation analysis. Results No significant differences in age, body mass index, heart rate, systolic blood pressure, and diastolic blood pressure were observed between the two groups (all P>0.05), while the waist-to-hip ratio (WHR) was higher in the case group than in the control group (P<0.05).The hormone level serological indicators TT and FAI were higher in the case group than in the control group, and SHBG was lower in the case group than in the control group (all P<0.05). The metabolism-related serum indicators LDL-C, HDL-C, FPG, triglycerides, and total cholesterol levels were not statistically different between the two groups (all P>0.05), and serum FINS, HOMA-IR, and Hcy levels were significantly higher in the case group than in the control group (all P<0.05).No significant difference in carotid artery diameter was observed between the case group and control group (P>0.05). The carotid artery displacement in the case group was significantly smaller than that in the control group (P<0.05), and carotid IMT, hardness coefficient, and pulse wave propagation velocity were greater in the case group than in the control group (all P<0.05). The carotid elastic stiffness coefficient was positively correlated with WHR, TT, SHBG, FAI, FINS, HOMA-IR and Hcy to varying extents and negatively correlated with SHBG. Conclusion In non-obese PCOS patients with no metabolic or cardiovascular disease, the carotid stiffness coefficient was increased and correlated with indicators of hyperandrogenism, insulin resistance, and hyperhomocysteinemia.